2021
DOI: 10.3390/ijms222111720
|View full text |Cite
|
Sign up to set email alerts
|

Lipedema and the Potential Role of Estrogen in Excessive Adipose Tissue Accumulation

Abstract: Lipedema is a painful fat disorder that affects ~11% of the female population. It is characterized by bilateral, disproportionate accumulation of subcutaneous adipose tissue predominantly in the lower body. The onset of lipedema pathophysiology is thought to occur during periods of hormonal fluctuation, such as puberty, pregnancy, or menopause. Although the identification and characterization of lipedema have improved, the underlying disease etiology remains to be elucidated. Estrogen, a key regulator of adipo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 75 publications
3
32
0
5
Order By: Relevance
“…Potentially, there is a disbalance between oestrogen receptors (ER alpha and ER beta) in adipose tissue of lipoedema affected certain areas, occurring as a result of faulty expression of oestrogen receptors. It can explain the abnormal proliferation of adipose tissue in the affected areas [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Potentially, there is a disbalance between oestrogen receptors (ER alpha and ER beta) in adipose tissue of lipoedema affected certain areas, occurring as a result of faulty expression of oestrogen receptors. It can explain the abnormal proliferation of adipose tissue in the affected areas [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, the demonstration of increased ZNF423 expression in lipedema-derived SVF, EC and PC provides for the first time a potential link of estrogen to preadipocyte commitment in lipedema. Katzer et al recently proposed that estrogen-mediated dysregulation of lower body fat accumulation in lipedema might be explained by a higher ERα/ERβ ratio or an increased production of steroidogenic enzymes, like aromatase, leading to a paracrine signaling and ERα activation among local adipocytes [12]. Indeed, we observed increased aromatase (CYP19A1) gene expression in lipedema thigh AT, which is also roughly reflected in the SVF, a cell population that does not contain mature adipocytes.…”
Section: Discussionmentioning
confidence: 49%
“…Bauer et al reported an increased IL-8 concentration in CM of undifferentiated ASC from lipedema patients, which decreased upon adipogenic stimulation to the equally low levels of the control cells [46]. The significant reduction of IL-8 secreted by lipedema SVF may correlate with higher local estradiol levels, which we and others have implicated with lipedema formation [12]. In the context of breast cancer cell lines, IL-8 has been identified as a regulatory target of estrogen receptor α and inhibited IL-8 levels as key factor for limited angiogenesis and tumor invasion [52].…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…[ 2 , 30 , 36 , 37 , 38 ]. Finally, lipedema almost exclusively occurs in females, has a strong familial history, and symptoms onset around periods of hormonal change (i.e., puberty, pregnancy, menopause), suggestive of estrogen-driven disease mechanisms and heritable traits [ 39 , 40 ].…”
Section: Clinical Criteria and Symptomatologymentioning
confidence: 99%